CO0002 LOSS OF SELF-TOLERANCE IN SARS-COV-2 INFECTION: IMMUNOLOGICAL ASSESSMENT OF A CONVALESCENT COHORT. (13th June 2020) - Paglionico, A.; Varriano, V.; Tolusso, B.; Alivernini, S.; Petricca, L.; Natalello, G.; Gigante, L.; Bosello, S. L.; Martone, A. M.; Landi, F.; Gremese, E.
Abstract : Background: Some infectious agents may act as inducers of autoimmune conditions 1 . Despite SARS-CoV-2 infection can induce autoimmune phenomena in infected people 2, individual risk factors or underlining mechanisms leading to loss of immunological tolerance are still unknown. Objectives: To assess the rate of development of autoantibodies in convalescent SARS-CoV-2 patients and their relation on infection clinical course and disease parameters. Methods: One-hundred and nine convalescent SARS-CoV-2 patients were studied and underwent multidisciplinary assessment in a Day Hospital clinical setting. For each patient, demographic, clinical and immunological data were collected and, at study entry, autoimmune profile [antinuclear antibodies (ANAs), antibodies reacting with extractable nuclear antigens (anti-ENA), antineutrophil cytoplasmic antibodies (ANCAs), Lupus anticoagulant (LA), anticardiolipin antibodies (aCL) IgM and IgG, anti-β2 glycoprotein I (anti-β2GPI) IgM and IgG] was assessed by Fluorescent immunoassay. Moreover, IL-6 plasma levels were assessed by ELISA (ELLA). Results: After a median time from hospitalization for SARS-CoV-2 infection of 53.3 ± 0.9 days, 55(50.5%) SARS-CoV-2 convalescent patients showed the positivity (AB pos ) of at least one autoantibody. In particular, 31(28.4%) were positive for LA, 11(10.1%) for IgM-RF, 8(7.3%) for ANA and 6(5.5.%) for IgG-aCL whilst less than 2% showed other autoantibody positivities (IgM-aCL, IgG-anti-β2GPI, ENA, ACPA, c-ANCA, Scl70 and RNP). Analyzing the patient-related characteristics associated with the development of autoimmunity, convalescent male patients were more likely characterized by the development of antiphospholipid antibodies (aPL) (37.3%) than female (16.7%; p=0.02). Considering the disease-related characteristics, convalescent SARS-CoV-2 patients who experienced severe pneumonia (i.e., oxygen support need) during hospitalization, more likely received IL-6R-inhibitor administration (47.3%) and developed more than one autoantibody (87.5%) (aPL + another AB) than convalescent SARS-CoV-2 patients who did not need oxygen support [(12.5%; p=0.02) (OR95%IC: 9.5(1.4-109.1)] or IL-6R-inihibitor (1.9%; p<0.001). Finally, assessing cytokines plasma levels in convalescent SARS-CoV-2 patients stratified based on the development of autoantibodies we found that, despite a significant reduction of IL-6 plasma levels from hospitalization, convalescent SARS-CoV-2 patients who developed autoantibody positivity had higher IL-6 plasma levels (8.5 ± 2.5 pg/ml) than convalescent SARS-CoV-2 AB neg patients (5.6 ± 1.5 pg/ml; p=0.07), mostly if considered autoantibodies other than aPL (15.4 ± 7.7 pg/ml)(p=0.01). Conclusion: Loss of self-tolerance is a common phenomenon in the medium-term follow-up of SARS-CoV-2 convalescent patients whose occurrence is dependent by a severe disease course and by an aberrant host inflammatory response. Long-term follow-up will reveal AB persistency and their clinical impact. References: [1]Barzilai O, et al. Current Opinion in Rheumatology 2007. [2]Zhou Y, et al. Clin Transl Sci. 2020. Disclosure of Interests: None declared